2021
DOI: 10.1136/rmdopen-2020-001555
|View full text |Cite
|
Sign up to set email alerts
|

ANCA-associated renal vasculitis is associated with rurality but not seasonality or deprivation in a complete national cohort study

Abstract: BackgroundSmall studies suggest an association between ANCA-associated vasculitis (AAV) incidence and rurality, seasonality and socioeconomic deprivation. We examined the incidence of kidney biopsy-proven AAV and its relationship with these factors in the adult Scottish population.MethodsUsing the Scottish Renal Biopsy Registry, all adult native kidney biopsies performed between 2014 and 2018 with a diagnosis of granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) were identified. The Scott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…A previous investigation indicated that ultraviolet radiation has an inverse correlation with the incidence of AAV, suggesting that seasonal variation could be related to disease incidence ( 19 ). Nonetheless, in our study, while the number of AAV cases was highest in March, the influence of season on the incidence of AAV was not significant, which was found similar in a recent national Scottish registry-based study, confirming a non-significant association between seasonality and AAV incidence ( 20 ). On our study, the overall incidence and prevalence of AAV seemed to increase gradually during the observation period.…”
Section: Discussionsupporting
confidence: 87%
“…A previous investigation indicated that ultraviolet radiation has an inverse correlation with the incidence of AAV, suggesting that seasonal variation could be related to disease incidence ( 19 ). Nonetheless, in our study, while the number of AAV cases was highest in March, the influence of season on the incidence of AAV was not significant, which was found similar in a recent national Scottish registry-based study, confirming a non-significant association between seasonality and AAV incidence ( 20 ). On our study, the overall incidence and prevalence of AAV seemed to increase gradually during the observation period.…”
Section: Discussionsupporting
confidence: 87%
“…Seasonality has also been investigated as a clue to infection; however, no clear pattern has been observed. European studies from the 1990s suggested a trend towards an increase in GPA in the winter 123 , 125 , whereas more recent studies have suggested a summer link or no association 126 , 127 , which might reflect differences in case definition by date of symptom onset or date of diagnosis. A study looking at health-care events occurring prior to a diagnosis of GPA in a UK general practice database did not report any health events that predicted subsequent development of vasculitis 128 .…”
Section: Small Vessel Vasculitismentioning
confidence: 96%
“…Other reported risk factors include rural living and farming 131 , 132 . Social factors have also been investigated, but no clear association with socio-economic status has so far been demonstrated, possibly reflecting differences in case definition (such as renal versus non-renal vasculitis) and assessment of socioeconomic status 127 .…”
Section: Small Vessel Vasculitismentioning
confidence: 99%
“…Studies in Scotland, Germany, and Canada showed that the incidence of AAV in rural areas is higher than that in cities. This may be related to environmental pollutants and pesticide exposure in remote areas (68,72,78,79). Additionally, a large Swedish case-control study (73) found no association between occupation and GPA (Table 1).…”
Section: Air Pollutionmentioning
confidence: 99%